2021
DOI: 10.1111/pce.14119
|View full text |Cite
|
Sign up to set email alerts
|

The phenylpropanoid pathway inhibitor piperonylic acid induces broad‐spectrum pest and disease resistance in plants

Abstract: Although many phenylpropanoid pathway-derived molecules act as physical and chemical barriers to pests and pathogens, comparatively little is known about their role in regulating plant immunity. To explore this research field, we transiently perturbed the phenylpropanoid pathway through application of the CINNAMIC ACID-4-HYDROXYLASE (C4H) inhibitor piperonylic acid (PA). Using bioassays involving diverse pests and pathogens, we show that transient C4H inhibition triggers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 96 publications
(145 reference statements)
2
33
0
Order By: Relevance
“…Lignified walls prevent pathogen infections by acting as a non-degradable mechanical barrier. The regulation of secondary metabolism genes in BRS may be a response to nematode migration and necrosis, as seen in plant–herbivore interactions [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lignified walls prevent pathogen infections by acting as a non-degradable mechanical barrier. The regulation of secondary metabolism genes in BRS may be a response to nematode migration and necrosis, as seen in plant–herbivore interactions [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plant-pathogen interaction and defense response would help DXWR survive under biotic stress ( Kushalappa and Gunnaiah, 2013 ). Phenylpropanoid which was a rich source of secondary metabolites in plants, together with plant hormone, played important roles in plant growth, development, and defense ( Desmedt et al, 2021 ; Dong and Lin, 2021 ). Moreover, starch and sucrose metabolism was the vital pathway in the process of rice grain filling, which could finally affect the yield ( Fan et al, 2019 ; Jiang et al, 2021 ; Mathan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observation that blocking PAL does not enhance susceptibility, it is likely that different metabolites could even play opposite roles in plant susceptibility or defense. Our recent research revealed that temporary perturbation of the phenylpropanoid pathway leads to a general reprogramming of the plant defense metabolome, and broad-spectrum-induced resistance in tomato (Desmedt et al, 2021). Which metabolite(s) is/are responsible for this IR remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%